Pengoptimalan Profil Kelembagaan sebagai Upaya Pengembangan Bisnis BUMDes di Kalurahan Hargorejo - Atmojo, Muhammad Eko; Sofyan, Nur; Kamil, Muhammad; Perdana, Vicky Alfitra (BERDIKARI, 2024)
Village-Owned Enterprises (BUMDes) is a village business managed by the Village Government, and has the status of a legal entity, which is formed in accordance with the needs and potential of the Village. Technological developments that are increasingly advanced certainly also need to be utilised properly by all circles and institutions, to facilitate life processes. However, in its development, BUMDes Kalurahan Hargorejo did not make good use of the potential of digital media for the branding and marketing of its business units. This condition is due to the lack of access and understanding of BUMDes members to digital media. This certainly has an impact on the lack of optimal business management carried out so that it has an impact on the internal economic turnover of the institution. This activity has activities that are offered as solutions to problems, namely social media optimisation workshops, and assistance in making BUMDes profiles. In addition, there are outputs from this activity, namely scientific publications, mass media publications, and BUMDes profile documents. In the end, it is hoped that this programme can have good sustainability in order to achieve an independent and competitive BUMDes Hargorejo in supporting local economic development